Analisis Usaha Pengembangan Agroforestri Pada Hutan Kemasyarakatan (HKm) Melalui Pinjaman Kredit Usaha Rakyat (KUR) di Desa Air Terjun Kabupatan Kerinci Provinsi Jambi - Fazriyaz, Fazriyaz; Ahyauddin, Ahyauddin; Nurmansah, Rahmad; Putri, Adela Salsabila (Jurnal MeA (Media Agribisnis), 2024)
Community Forestry is one of the social forestry schemes in an effort to resolve land conflicts and forest and land rehabilitation (RHL) problems in State Forest Areas. Apart from that, Community Forests also provide opportunities for local communities who have lived around forest areas for generations to be able to use area land for business activities in planting both seasonal crops and forestry plants. The fundamental problem in supporting communities in managing state forest land is the lack of capital to invest as output costs during management activities. Through the KUR loan facility, it is hoped that people who are members of social forestry management groups can make it easier to use as initial capital to invest. This research will be carried out in the Community Forest (HKm) in Air Terjun Village, Kerinci Regency, Jambi Province. This research consists of several studies and uses analysis of several investment criteria, including Net Present Value (NPV), Net Benefit Ratio (B/C Ratio), Internal Rate of Return (IRR), which is an indicator to find out the level of efficiency of an investment, and Payback Period (PP). Analysis of the feasibility of cultivating agroforestry patterns shows that the Net Present Value (NPV) value in years 1 to 10 is greater than 0, which means it is worth cultivating, while the Net B/C Ratio calculation value in years 1 to The 10th year gets a value greater than 1, meaning it is worth pursuing, while the IRR value in years 1 to 10 gets a percentage value greater than 10%, meaning it is worth investing in. Meanwhile, the Payback Period value (investment return time) is 0.23 years.